AB0542 Disease Flares in a Monocentric Cohort of Patients with Systemic Lupus Erythematosus: Incidence, Clinical and Laboratory Characteristics, Associated Factors and Treatment. (9th June 2015) - Floris, A.; Piga, M.; Massa, L.; Vacca, S.; Corraine, M.; Vacca, A.; Garau, P.; Ibba, V.; Cauli, A.; Mathieu, A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic inflammatory disease which is characterized by disease flares during maintenance treatment. Objectives: To evaluate the incidence of flares, the possible association with clinical and serological factors and their therapeutic management in a monocentric SLE cohort. Methods: Clinical and laboratory data of 143 patients with SLE, diagnosed between 1997 and 2012 according to the 1982 ACR/ARA and followed-up at the Centre of Rheumatology of the University Hospital of Cagliari, Italy, were retrospectively collected. For the purposes of the study a flare was defined and classified as severe or mild/moderate, according to a modified version of the SELENA-SLEDAI index. For each patient demographic, clinical (in agreement with the BILAG2004-index) and laboratory features as well as medication ongoing at enrolment and in the 6 months prior to the flares were recorded. Then, all these were used as covariates in the univariate statistical analysis. Results: During the follow-up (5.43±4.2yr) at least one disease flare was recorded in 41 out of 143 patients (28, 7%) for a total of 63 flares, with an incidence rate of 8.1 flares per 100 patient-years. 53.9% of the flare was classified as severe. Active clinical manifestations at the time of flare were: musculoskeletal (66.7%), mucocutaneous (41.3%), systemic (38.1%), hematologic (31.7%), vasculitic-vasculopathic (25.4%), kidney (22.2%), neurological (22.2%), cardio-respiratory (4.7%). At the univariate statistical analysis, the factors significantly associated with the development of flare were: level above cut off values of 7 IU/dl for Farr assay anti-dsDNA (OR: 2.66; p=0.0272) and low dose corticosteroidal monotherapy in the absence of combined treatment with immunosuppressive drugs (OR: 3.42; p=0.0080). From a sub-analysis performed on 29 flares, for which it was possible to review the anti-dsDNA changes in at least two measurements during the six months preceding flare, in 17 cases (59%) there was a rise in anti-dsDNA level greater than 20% before or concurrently of flares. As regards the therapeutic approach in 79.4% of cases the therapy with immunosuppressant or antimalarials has been modified: in the 47.6% of cases a new drug was added, in 17.5% was switched, in 15.0% the dosage was increased. Only the 30% of flares treated by modification of therapy with immunosuppressants, with or without increase of dosage of corticosteroids, was followed by another flare in the time interval of the study. Fifteen changes of therapy with immunosuppressant (with or without increase of dosage of corticosteroids) for the isolated increase in anti-DNA were recorded: only one of these cases was followed by a flare: a significant difference with the number of flares which followed the adjustement of therapy at clinical relapse (p=0, 0482) was found. Conclusions: In our series the increase of anti-dsDNAds antibodies (Farr assay) levels above 20% of the six-months previous values or the maintenance treatment with corticosteroidal monotherapy alone were predictors of the occurrence of flares. The study highlights the need for close follow up of anti-dsDNA antibodies levels and the importance of immunosuppressants and/or antimalarials for the maintenance therapy. Disclosure of Interest: None declared